2011
DOI: 10.1590/s0103-90162011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the stress-inducible transcription factor SsNAC23 in sugarcane plants

Abstract: Stresses such as cold and drought can impair plant yield and induce a highly complex array of responses. Sugarcane (Saccharum spp.) is cultivated in tropical and subtropical areas and is considered a coldsensitive plant. We previously showed that cold stress induces the expression of several genes in in vitro sugarcane plantlets. Here we characterize one of those genes, SsNAC23, a member of the NAC family of plant-specific transcription factors, which are induced by low temperature and other stresses in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…One of the targets for this miRNA is a protein containing a NAC domain. Proteins from this family are known to be induced by diverse abiotic factors (Ditt et al 2011; Hegedus et al 2003; Sun et al 2011). Although we found a high variability in the expression of the target gene in the field-grown plants, the ssp-miR160-seq 1 and target gene expression profiles indicated that LT plants repress and have lower levels of the target gene, while the opposite profile was observed in HT plants.…”
Section: Discussionmentioning
confidence: 99%
“…One of the targets for this miRNA is a protein containing a NAC domain. Proteins from this family are known to be induced by diverse abiotic factors (Ditt et al 2011; Hegedus et al 2003; Sun et al 2011). Although we found a high variability in the expression of the target gene in the field-grown plants, the ssp-miR160-seq 1 and target gene expression profiles indicated that LT plants repress and have lower levels of the target gene, while the opposite profile was observed in HT plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of NTL1 and NTL11 genes were observed after heat stress, while NTL4 and NTL7 were exhibited specifically by low temperature in Arabidopsis [62]. In sugarcane, SsNAC23 expression was induce in response to low temperature stress [66]. ANAC019, member of NAC TFs, has been observed to enhance the ability of Arabidopsis to cold tolerance by inducing the expression of cold responsive marker gene COR47 [55].…”
Section: Function and Expression Pattern Of Nac Tfs Under Abiotic Strmentioning
confidence: 99%
“…Each of experiment was replicated three times. Bars shown means ± SD TF, SsNAC23, is induced by low temperatures in sugarcane (Ditt et al 2011). Here, we found that the expression levels of two NAC TFs increased by cold treatment in ROC22 but remained unchanged in GT42 (Table 2, Fig.…”
Section: Transcription Factors May Play Roles In Regulating Cold Resistance In Sugarcane Budsmentioning
confidence: 53%